Detection and genetic characterization of Porcine circovirus type 3 in Italy. Issue 6 (17th September 2017) - Faccini, S.; Barbieri, I.; Gilioli, A.; Sala, G.; Gibelli, L. R.; Moreno, A.; Sacchi, C.; Rosignoli, C.; Franzini, G.; Nigrelli, A.
Summary: Porcine circovirus type 3 (PCV3) was recently proposed as a new porcine circovirus. It has been described by researchers in the USA and China and associated with porcine dermatitis and nephropathy syndrome, reproductive failure and systemic inflammation disease. The study reports the occurrence of the new virus in Italy. PCV3 was detected in the tissues of foetuses and stillborn piglets coming from two farms located in the Po Valley. The genome sequences of the two Italian strains share 99.7% to 97.8% of nucleotide identity with those available in GenBank. Results strengthen the hypothesis of PCV3 as a new emerging porcine circovirus, widespread all over the world. It follows the urgency of investigating in depth epidemiology and pathogenicity associated with this new virus.